2011
DOI: 10.1158/1078-0432.ccr-11-1026
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alteration of PRKCDBP in Colorectal Cancers and Its Implication in Tumor Cell Resistance to TNFα-Induced Apoptosis

Abstract: Purpose: PRKCDBP is a putative tumor suppressor in which alteration has been observed in several human cancers. We investigated expression and function of PRKCDBP in colorectal cells and tissues to explore its candidacy as a suppressor in colorectal tumorigenesis.Experimental Design: Expression and methylation status of PRKCDBP and its effect on tumor growth were evaluated. Transcriptional regulation by NF-kB signaling was defined by luciferase reporter and chromatin immunoprecipitation assays.Results: PRKCDBP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 37 publications
4
53
0
Order By: Relevance
“…Discussion TNF-a is a critical proinflammatory cytokine, and its downregulation in the colonic mucosa is associated with regressed inflammation in patients with moderate-to-severe UC [13,15]. A recent study showed that PRKCDBP, a proapoptotic tumor suppressor gene, is a direct transcriptional target of TNF-a/NF-jB signaling, and its expression is frequently lost or downregulated in human colorectal cancer [22]. Despite this, the expression status of PRKCDBP in human IBD has not yet been defined.…”
Section: Clinical Outcomes In the First Year According To Prkcdbp Expmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion TNF-a is a critical proinflammatory cytokine, and its downregulation in the colonic mucosa is associated with regressed inflammation in patients with moderate-to-severe UC [13,15]. A recent study showed that PRKCDBP, a proapoptotic tumor suppressor gene, is a direct transcriptional target of TNF-a/NF-jB signaling, and its expression is frequently lost or downregulated in human colorectal cancer [22]. Despite this, the expression status of PRKCDBP in human IBD has not yet been defined.…”
Section: Clinical Outcomes In the First Year According To Prkcdbp Expmentioning
confidence: 99%
“…PRKCDBP expression is frequently downregulated in many types of malignancy, including colorectal cancer, due to aberrant promoter CpG site hypermethylation [18][19][20][21]. Activation of PRKCDBP induces cell cycle arrest and apoptosis by enhancing p53 protein stability, while its inactivation contributes to tumor growth and increased resistance to TNF-a-induced apoptosis [22]. It was also demonstrated that PRKCDBP is a transcription target of TNF-a, which plays a crucial role in colonic inflammation and tumorigenesis [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumor suppressor genes are involved in regulating cellular differentiation, senescence, apoptosis, cell cycle arrest, DNA repair, microtubule dynamics and genomic instability [8][9][10][11][12][13]. Silencing of tumor suppressor genes mediated by DNA methylation is a hallmark of human cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…MOAP1 gene encodes protein which functionally mediates caspase-dependent apoptosis by its interaction with apoptosis regulator protein [37]. The gene encoding protein kinase C delta binding protein, PRKCDBP expression has been shown to induce the G1 cell-cycle arrest and increased cellular sensitivity to various apoptotic stresses [38]. The expression of this protein was found to be down-regulated in various cancer cell lines, suggesting the possible tumor suppressor function of this protein.…”
Section: Discussionmentioning
confidence: 99%